Syndromic and Systemic Diagnoses Associated With Isolated Sagittal Synostosis. Issue 12 (December 2019) - Davis, Amani A.; Haredy, Mostafa M.; Huey, Jennifer; Scanga, Hannah; Zuccoli, Giulio; Pollack, Ian F.; Tamber, Mandeep S.; Goldstein, Jesse; Madan-Khetarpal, Suneeta; Nischal, Ken K.
Abstract : Background: Reports of systemic associations in patients with Isolated Sagittal Synostosis (ISS) are sparse. Craniofacial surgeons, and other providers, should be aware that a significant proportion of patients with ISS may have syndromic or systemic involvement. This study investigates the incidence of systemic disease and syndromic diagnosis in a cohort of patients presenting with ISS (ie, patients with sagittal synostosis without other sutural involvement). Methods: This study consists of a retrospective review of patients diagnosed with ISS between 2007 and 2017 at a single institution. Patients were divided according to onset (early <1 year, late >1 year) of ISS. Patient notes were examined for congenital anomalies, systemic conditions, and molecular testing. Only patients with isolated sagittal fusion—meaning, patients with sagittal synostosis and no other sutural involvement—were included. Results: Three hundred seventy-seven patients met the inclusion criteria: systemic conditions were identified in 188/377 (50%) of them. One hundred sixty-one patients with early onset (Group A), and 216 patients with late onset ISS (Group B) were identified. Systemic involvement was identified in 38% of Group A and 60% of Group B, which was statistically significant ( P < 0.001). Forty-eight of 377 (13%) of patients had a syndromic diagnosis, and 79% of these were confirmed via genetic testing. Thirty-five percent of patients were diagnosed with central nervous system anomalies and 16% had craniofacial anomalies. Conclusions: Nearly 50% of the patients initially diagnosed with ISS were found to have some form of systemic involvement. This supports affording full pediatric and genetic evaluation with molecular testing to these children.